2017
DOI: 10.1007/s00431-016-2831-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of definitions for the metabolic syndrome in adolescents. The HELENA study

Abstract: The different definitions do not classify the same adolescents as having MS and prevalence varied between diagnostic methods. The modified NCEP-ATP and the AHA definitions were most analogous in defining subjects as having metabolic syndrome or not. What is known? • Metabolic syndrome is not only a problem of adulthood but is already present in children and adolescents. • Several diagnostic methods are used to define metabolic syndrome in adolescents. What is new? • Comparing the most frequently used definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
2
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
5
33
2
10
Order By: Relevance
“…Nevertheless, the exact prevalence of MetS is difficult to identify since the prevalence was distinctive according to each definition, being from 1.6% (IDF criteria) to 5.1% (Cook et al [29] criteria). These findings are consistent with previous studies that showed how the prevalence was from 1.7% (IDF [32] criteria) up to 11% (de Ferranti et al [30] criteria) [50,51,56]. In this sense, this statement was also reported by González-Jiménez et al [55] that showed how using IDF criteria in a sample of 976 Spanish children aged 10-15 years, the prevalence of MetS was 4.4% (3.85% in girls and 5.8% in boys).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the exact prevalence of MetS is difficult to identify since the prevalence was distinctive according to each definition, being from 1.6% (IDF criteria) to 5.1% (Cook et al [29] criteria). These findings are consistent with previous studies that showed how the prevalence was from 1.7% (IDF [32] criteria) up to 11% (de Ferranti et al [30] criteria) [50,51,56]. In this sense, this statement was also reported by González-Jiménez et al [55] that showed how using IDF criteria in a sample of 976 Spanish children aged 10-15 years, the prevalence of MetS was 4.4% (3.85% in girls and 5.8% in boys).…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, this statement was also reported by González-Jiménez et al [55] that showed how using IDF criteria in a sample of 976 Spanish children aged 10-15 years, the prevalence of MetS was 4.4% (3.85% in girls and 5.8% in boys). Moreover, the Helena Study [56] also showed the variation depending on the definition. This study showed how a cohort of 3,528 adolescents aged 12.5-17.5 years from 10 European countries reported a prevalence of MetS of 2.7% and 3.5% according to IDF and NCEP-ATPIII, respectively [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the prevalence of MetS was significantly higher in girls compared to boys, which is in contrast to previous studies in which American [25], Iranian [26] and Chinese [27] children were evaluated. These differences could perhaps be explained by the use of different criteria to define the MetS [28,29]. In any case, further studies are needed to explore the possible conditioning factors of these sex-based differences among the pediatric population in general.…”
Section: Discussionmentioning
confidence: 99%
“…A consensus definition for MetS in children and adolescents has not yet been developed. There are currently at least 40 unique definitions of MetS for this age group [ 9 ], and the prevalence of MetS varies depending on the definition used [ 32 ]. Weiss and colleagues [ 33 ] argued that the environment plays a major role in the development of MetS, in particular the typical Western diet, which has now been adopted globally due to palatability and price.…”
Section: Introductionmentioning
confidence: 99%